Synthesis, characterization and thermal behaviour of solid-state compounds of benzoates with some bivalent transition metal ions - Siqueira, Adriano B. [UNESP]; Ionashiro, Elias Y. [UNESP]; Carvalho, Cláudio T. de [UNESP]; Bannach, Gilbert [UNESP]; Rodrigues, Emanuel C. [UNESP]; Ionashiro, Massao [UNESP] (Sociedade Brasileira de Química, 2007)
Solid-state MBz compounds, where M stands for bivalent Mn, Fe, Co, Ni, Cu and Zn and Bz is benzoate, have been synthesized. Simultaneous thermogravimetry and differential thermal analysis (TG-DTA), differential scanning calorimetry (DSC), infrared spectroscopy and complexometry were used to characterize and to study the thermal behaviour of these compounds. The procedure used in the preparation of the compounds via reaction of basic carbonates with benzoic acid is not efficient in eliminating excess acid. However the TG-DTA curves permitted to verify that the binary compounds can be obtained by thermosynthesis, because the benzoic acid can be eliminated before the thermal decomposition of these compounds. The results led to information about the composition, dehydration, thermal stability, thermal decomposition and structure of the isolated compounds. on heating, these compounds decompose in two (Mn, Co, Ni, Zn) or three (Fe, Cu) steps with formation of the respective oxide (Mn3O4, Fe2O3, Co3O4, NiO, CuO and ZnO) as final residue. The theoretical and experimental spectroscopic studies suggest a covalent bidentate bond between ligand and metallic center.
Keywords: bivalent transition metals; benzoate; thermal behaviour